Sriwijaya Festival Poster for the 2023-2025 Period as a Cultural Communication Medium - Mukhsin Patriansah; Heri Iswandi; Haniyah Ashillah Putri; Veni Nabila Az-zahra (Sanggitarupa, 2026)
The Sriwijaya Festival poster is a visual communication medium that serves to convey cultural messages to the public. This study aims to analyze the Sriwijaya Festival poster for the 2023–2025 period as a cultural communication medium in representing the history and cultural values ​​of Sriwijaya as a great maritime kingdom in Southeast Asia. This research uses a visual analysis approach and formal analysis to see the elements and principles of design in detail and comprehensively. In addition, the author also uses Stuart Hall's representation theory approach, namely reflective, intentional, and constructionist to examine cultural messages. The research method used is descriptive qualitative, for Data collection techniques are carried out through observation, interviews, and literature studies. Meanwhile, the stages of data analysis in this study, begin with description, then data analysis and interpretation. The results show that the Sriwijaya Festival poster not only functions as a medium for event information, but also as a means of constructing cultural meaning that displays local identity, historical values, and symbols of Sriwijaya culture. Through the use of visual and symbolic elements, the posters build a cultural narrative that strengthens the image of the Sriwijaya Festival as a representation of regional cultural heritage. Thus, the Sriwijaya Festival poster can be understood as an effective cultural communication medium for conveying messages, shaping perceptions, and introducing the richness of local culture to the wider public.